INNOVATIVE MARKETING AND CREATION OF NEW OPPORTUNITIES - Daminov, Jasur; Xudoyarov, Rashid; Rashidov, Abror (Science technology&Digital finance, 2023)
This article presents innovative marketing and marketing innovations, their benefits for our society, as well as recommendations on modern marketing strategies.